2017 Report to Readers. Issue 2 (1st April 2018) - Brown, Stephen J.
Abstract : In 2017, we published 22 peer-reviewed articles, including 18 research articles and four Perspectives pieces, on a broad range of topics related to the practice of investment management. We also published one Viewpoint, one Editor's Corner, and an interview with Nobel Prize winner Harry Markowitz. This variety of content continues to provide unique opportunities for readers to advance their knowledge and understanding of the practice of investment management and to keep abreast of new research and ideas.